Pembinaan Etika Komunikasi, Ketahanan dan Kesehatan Keluarga, serta Manajemen Keuangan: Pembinaan Majelis dan Jemaat di Gereja Toraja Kuala Lumpur Malaysia - Ktut Silvanita Mangani; Djoys A. Rantung; Bernadetha Nadeak; Mesta Limbong (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Abstract In performs its services, the church needs to implement communication ethics so that good and understandable communication occurs. The church needs to organize with all the risks it faces. This shows the need for good management, including financial management in the church. Apart from that, family resilience and health are also needed in building relationships between family members in order to create harmonious relationships in building a Christian congregation. This community service activity aims to provide an understanding of communication ethics, family resilience and health, as well as financial management in the church. Using lecture and discussion methods. This activity received a very good response from all participants as seen from their enthusiasm in participating in this training. They also hope that UKI can provide further training and other activities.